Development of failure mitigation technologies for improving resilience of nuclear structures - Kasahara, Naoto; Yamano, Hidemasa; Nakamura, Izumi; Demachi, Kazuyuki; Sato, Takuya; Ichimiya, Masakazu (The International journal of pressure vessels and piping, 2024)
After the Fukushima daiichi nuclear power plant accident, various countermeasures were taken for Beyond Design Basis Events (BDBE) in the system safety field. These included portable devices, additional backup facilities and accident management. They are different from approaches for Design Basis Events (DBE). In the field of structural mechanics; however, efforts were focused on strengthening to prevent failures for both DBE and BDBE in the same way. This approach will lead to limitless requirements for strength and expensive plants. As a breakthrough approach in structural mechanics for BDBE, we propose failure mitigation methods through the application of passive safety structures, where preceding failures release loadings and mitigate subsequent failures. When preceding failure modes have small impacts on safety performance, such as small deformation and crack initiation, and subsequent ones are catastrophic modes such as collapse and break, the passive safety structure improves safety and resilience. This idea is the utilization of passive characteristics of structures without additional equipment and electric power, allowing for simple and reliable plants. To demonstrate this idea, passive safety structures were applied to next-generation fast reactors, subject to high temperature and low-pressure conditions. In the case of loss-of-heat-removal accidents, high temperature conditions accelerate the creep deformation of structures. When deformation redistributes loadings and reduces stresses at important positions such as coolant boundaries, progression to creep rupture of boundaries can be mitigated. When an excessive earthquake occurs, plastic deformation and buckling become dominant, due to low pressure and, therefore, a thin-wall structure. The above-mentioned failure modes reduce rigidity and natural frequency. When the natural frequency becomes lower than the input frequency, vibration energy is hardly transferred to structures and the subsequent failures of structures, such as collapse and break, are mitigated. •Failure mitigation methods for Beyond Design Basis Events were proposed.•Core technologies are passive safety structures, where preceding failures release loadings and mitigate consequent failures.•Example applications of passive safety structures were demonstrated for fast reactors under high temperature accidents and excessive earthquakes.•Above safety characteristics were validated through structural tests and inelastic analyses.